FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL PUSKESMAS LABAKKANG KEC. LABAKKANG KAB. PANGKAJENE DAN KEPULAUAN - Aisyah aisyah (Stikes Graha Edukasi Makassar, 2021)
Objective: The purpose of this study was to determine the factors associated with the incidence of anemia in pregnant women. Methods: Case Control Study aims to find the relationship between the independent variable and the dependent variable. The population in this study were all pregnant women who had their pregnancy checked at the Labakkang Health Center, Kec. Labakkang Kab. Pangkajene and Islands in 2018. The sample in this study were all pregnant women who had their pregnancy checked and experienced anemia at the Labakkang Health Center, Kec. Labakkang Kab. Pangkajene and Islands in 2018 as many as 58 people with the sampling technique of Accidental Sampling. Results: 1) Based on the results of the chi-square analysis, the value of p = 0.000 is smaller than = 0.05, this means that Ho is rejected and Ha is accepted. Thus there is a relationship between the distance of pregnancy with the incidence of anemia. 2) Based on the results of the chi-square analysis, the value of p = 0.031 is smaller than = 0.05, this means that Ho is rejected and Ha is accepted. Thus there is a relationship between adherence to consuming Fe tablets with the incidence of anemia. 3) Based on the results of the chi-square analysis, the value of p = 0.526 is greater than = 0.05, this means that Ho is rejected and Ha is accepted. Thus there is no relationship between maternal parity and the incidence of anemia. 4) Based on the results of the chi-square analysis, the value of p = 0.001 is smaller than = 0.05, this means that Ho is rejected and Ha is accepted. Thus there is a relationship between education and the incidence of anemia. Conclusion: 1) There is a relationship between the distance of pregnancy with the incidence of anemia. 2) There is a relationship between adherence to consuming Fe tablets with the incidence of anemia. 3) There is no relationship between maternal parity and the incidence of anemia. 4) There is a relationship between maternal education and the incidence of anemia